2020
DOI: 10.1002/jsfa.10526
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow trout (Oncorhynchus mykiss) identification in processed fish products using loop‐mediated isothermal amplification and polymerase chain reaction assays

Abstract: BACKGROUND Financial loss and health risk caused by the substitution of rainbow trout for other salmonid species have become a common issue around the world. The situation could be further exacerbated in China by the ‘abused’ common name of San Wen Yu (the corresponding Chinese ideogram 三文鱼) for salmonids, considering the absence of a standardized naming system for seafood species. To prevent such episodes, the present study aimed to develop novel loop‐mediated isothermal amplification (LAMP) and polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…1 ). Particularly, LAMP primers (FIP, BIP, F3, B3 and LB) were obtained from our previous studies ( Li et al, 2022 , Xiong et al, 2020 ), with one exception of R-LB designed in the present work ( Table 1 ). In order to meet the labeling criteria in self-quenched approach ( Gadkar et al, 2018 ), the 3′ end of S-BIP, R-FIP, and R-LB was slightly modified, and two different fluorophores (FAM and ROX) were attached ( Table 1 ), which are self-quenched in unbound state and become de-quenched after binding to the dumbbell-shaped target DNA specifically ( Li et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). Particularly, LAMP primers (FIP, BIP, F3, B3 and LB) were obtained from our previous studies ( Li et al, 2022 , Xiong et al, 2020 ), with one exception of R-LB designed in the present work ( Table 1 ). In order to meet the labeling criteria in self-quenched approach ( Gadkar et al, 2018 ), the 3′ end of S-BIP, R-FIP, and R-LB was slightly modified, and two different fluorophores (FAM and ROX) were attached ( Table 1 ), which are self-quenched in unbound state and become de-quenched after binding to the dumbbell-shaped target DNA specifically ( Li et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, LAMP has gained in popularity in recent decades and is one of the most widely researched methods for species identification [ 11 , 23 ]. Thus, it has already been used to detect several fish species such as eel ( Anguilla anguilla ) [ 12 ], salmon ( Oncorhynchus mykiss ) [ 24 ], cod ( Gadus morhua ) [ 14 ] and skipjack tuna ( Katsuwonus pelamis ) [ 15 ]. LAMP was applied successfully in various contexts and appears to be a fast and efficient alternative to PCR in the case of food fraud monitoring due to its low equipment requirements, easy handling and ability to be used in field [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the selection of LAMP primer design sites, to ensure the specificity of the primers, there should be a certain number of mismatches between the sequence bases of the target species and the closely related species to reduce nonspecific amplification. For example, Xiong et al (2020) found mismatch sites between Oncorhynchus mykiss and closely related species when designing LAMP primers for O. mykiss so that the primers were highly specific for O. mykiss. The G. infula LAMP primer set I designed in this study had some mismatches with other Gyromitra species at the 3' end of G.mol-F3/B3 and the 5' end of G.mol-F1c/ B1c, showing that the G. infula LAMP primers designed in this study had high specificity.…”
Section: Discussionmentioning
confidence: 99%